Gender mainstreaming in surveys - Nicot, Anne-Marie; Houtman, Irene L.D. (Dublin, 2006)
"This comparative analytical report provides a comparative overview of how gender mainstreaming is incorporated into national working conditions surveys, based on 12 national contributions. It investigates the conceptual and methodological framework of gender mainstreaming in surveys, as well as its implementation. The report then examines some of the survey findings on the respective situation of women and men regarding working conditions."